Teaching reading in junior high school - Yusma Rita Kurnia; Ni Luh Evit Erawati (English, 2018)
This study aims to determine the form of teaching reading at the level of Junior High School, especially in grade VII. The sample was taken at K. S. Junior High School of Denpasar. The analysis is limited to the type of reading, assignment given, and the micro and macro reading skills that need to be taught in Indonesian subjects. The data were analyzed and presented qualitatively according to the Assesing Reading theory (Brown, 2004). The results of this study show that teaching reading in Junior High School begin with the type of interactive and extensive reading. Interactive reading assignments applied are trough Editing (longer tasks), Scanning, and Ordering Tasks. While the extensive reading assignments are Skimming Tasks and Summarizing. Micro skills that need to be taught are mastering pieces of language with different lengths in short-term memory, reading at an efficient speed according to purpose, recognizing the word core and interpreting patterns or word order and its meaning systematically, recognizing the grammatical word class, cohesive device in discourse and its role in signifying the relationship between and among clauses. While the macro skills that need to be taught include recognizing the rhetorical form of written discourse and its significance for interpretation, the communicative function of the text, the unexplained context, summing up the relationship among events, causality, distinguishing literal and implicit meanings, developing and using reading strategies such as scanning and skimming, guessing the meaning of words from the context and interpreting the text.